ANALISIS KOMPETENSI PEDAGOGIK GURU DALAM PENERAPAN KURIKULUM MERDEKA DI SDN KADUBUNGBANG 1 - Nurmala, Neli; Robandi, Babang (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2025)
This study aims to analyze the pedagogical competence of teachers in implementing learning in the independent curriculum which includes understanding student characteristics, understanding learning theories, implementing learning, utilizing technology and information in learning, and evaluating independent curriculum learning at SDN Kadubungbang 1. The method used in this study is a qualitative method with a naturalistic analysis type. The sample of this study was teachers at SDN Kadubungbang 1. The instruments used included interview guidelines, observation sheets, and related documents. Data collection techniques used included interviews, observations, and documentation studies. Data analysis techniques used included data collection, data reduction, data presentation, and drawing conclusions. The conclusion of this study is that teachers at SDN Kadubungbang 1 have a basic understanding of the principles of the Independent Curriculum, especially related to differentiated learning in recognizing student character and the formation of Pancasila student profiles. Teachers are able to compile learning tools, such as teaching modules that are in accordance with the Independent Curriculum guidelines. However, some teachers still face obstacles in designing learning activities that are fully responsive to the needs, interests, and potential of students. The implementation of learning in the classroom shows that most teachers have tried to apply a student-centered approach. Keywords: Competence; Pedagogy; Independent Curriculum